ALK-Fusion Transcripts Can Be Detected in Extracellular Vesicles (EVs) from Nonsmall Cell Lung Cancer Cell Lines and Patient Plasma: Toward EV-Based Noninvasive Testing. - Sánchez-Herrero, Estela; Campos-Silva, Carmen; Cáceres-Martell, Yaiza; Robado de Lope, Lucía; Sanz-Moreno, Sandra; Serna-Blasco, Roberto; Rodríguez-Festa, Alejandro; Ares Trotta, Dunixe; Martín-Acosta, Paloma; Patiño, Cristina; Coronado, María José; Beneitez, Alexandra; et al. (Clinical Chemistry, 2022)
BACKGROUND: ALK rearrangements are present in 5% of nonsmall cell lung cancer (NSCLC) tumors and identify patients who can benefit from ALK inhibitors. ALK fusions testing using liquid biopsies, although challenging, can expand the therapeutic options for ALK-positive NSCLC patients considerably. RNA inside extracellular vesicles (EVs) is protected from RNases and other environmental factors, constituting a promising source for noninvasive fusion transcript detection. METHODS: EVs from H3122 and H2228 cell lines, harboring EML4-ALK variant 1 (E13; A20) and variant 3 (E6a/b; A20), respectively, were successfully isolated by sequential centrifugation of cell culture supernatants. EVs were also isolated from plasma samples of 16 ALKpositive NSCLC patients collected before treatment initiation. RESULTS: Purified EVs from cell cultures were characterized by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and flow cytometry. Western blot and confocal microscopy confirmed the expression of EV-specific markers as well as the expression of EML4-ALK-fusion proteins in EV fractions from H3122 and H2228 cell lines. In addition, RNA from EV fractions derived from cell culture was analyzed by digital PCR (dPCR) and ALK-fusion transcripts were clearly detected. Similarly, plasma-derived EVs were characterized by NTA, flow cytometry, and the ExoView platform, the last showing that EV-specific markers captured EV populations containing ALK-fusion protein. Finally, ALK fusions were identified in 50% (8/16) of plasma EV-enriched fractions by dPCR, confirming the presence of fusion transcripts in EV fractions. CONCLUSIONS: ALK-fusion transcripts can be detected in EV-enriched fractions. These results set the stage for the development of EV-based noninvasive ALK testing.